The Role of Psychoeducation Interventions in Preventing Schizophrenia Recurrence - Yessi Apriance; Andri Sujatmoko (HM Publisher, 2021)
Schizophrenia disorder is a neurodevelopmental brain disorder characterized by impaired neurotransmitter interactions in the central nervous system. This schizophrenic disorders require treatment aimed at overcoming the disruption of neurotransmitter interactions in the central nervous system. Psycho-education (PE) can not only be applied to individuals with schizophrenia but can also be applied to families and groups. PE is widely given to patients with psychiatric disorders, including family members and people with interest in treating these patients. This literature review aims to discuss the role of psycho-education in schizophrenic patients.